TRICHOGRAM OBSERVATION OF ORAL IVERMECTIN THERAPY IN SCABIOSIS AND OTITIS EXTERNA IN DOMESTIC CATS - Rafi Ahmad Farhan; Putu Devi Jayanti; I Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2025)
Scabiosis is a skin disease in cats caused by the Notoedres cati mite in the corneum layer of the skin. Apart from scabiosis, cats also often suffer from ear diseases, one of which is otitis externa which is caused by otodectes cynotis. aims to report and determine the success of therapy due to Notoedres cati and Otodectes cynotis mite infections in domestic cats. This article aims to report and determine the success of therapy due to infection by Notoedres cati and Otodectes cynotis mites in a 4 year old domestic cat weighing 3.6 kg. The case cat was rescued around Jalan Gunung Gede and had skin disease on the face and ears. Cats often scratch, especially at the ears. Physical examination showed that the skin and nails were abnormal and found crusting, hyperkeratosis, alopecia, scarring, and erythema. Physical examination of the ear is abnormal, there is dry blackish brown earwax. On skin examination using superficial skin scraping and deep skin scraping methods, Notoedres cati was found. Examination of the ear using the otic swab method revealed the presence of Otodectes cynotis. The results of observations on the 15th day showed changes with good hair growth and no hair breaks, the level of itching was no longer there, hyperkeratosis was no longer there, no scars, no erythema and crusts had greatly reduced and the ears were clean. cerumen. Things that must be considered are not releasing cats into the wild with the aim of not being infected with scabiosis again, maintenance management such as providing adequate and nutritious food, environmental cleanliness and maintenance tools, as well as the cleanliness of the cat's body need to be considered.